The Subjectivity on Multicultural Families : Q-Methodology - Sunyoung Jang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of this study are to understand the subjectivity of multicultural families perceived by nursing students, to describe the characteristics of each type, and also to understand the classification of multicultural families by applying the Q-methodology. Total of 20 students of the nursing department in A college were asked to classify total of 42 sentences of statements about multicultural families. The collected data was analyzed by using the QUANL PC Program. In the results of this study, the nursing students’ perception of multicultural families was divided into three factors. The types of subjectivity on multicultural families included the ‘type of accepting and acknowledging multicultural families’, the ‘type of seeking for institutional support’, and the ‘type of conservative perception’. This study provided the basic data of basic humanities and social science education for nurses and nursing students who would nurse multicultural families.